(untitled) (Sociologisk Forskning, 2016)
Practice as you preach? Gender scholars’ reflections on practising gender theory Being a gender scholar – to what extent is it possible to practice as you preach? This study investigates how gender scholars relate to using and practicing theoretical knowledge on gender.Ten in-depth interviews are conducted with gender scholars at Swedish universities. A semi-structured interview guide, based on ambitions, possibilities and obstacles regarding using theoretical knowledge in practice, is used. The results indicate that being a gender scholar is a highly reflective project, since it involves turning your gender theoretical gaze towards yourself. Practicing as you preach seems to be interpreted as undoing gender. Attempts to undo gender are said to be hindered by gender normative structures rendering gender scholar women and gender scholar men different possibilities to practice the undoing of gender. The analysis show that gender scholars perform a balancing act by adding some expressions for the opposite gender to their everyday doings and their physical appearance, thus combining a doing with an undoing of gender. The pace and force of change in these doings and undoings are rather small. Nevertheless, small as they may be, these steps are interpreted as part of a strategy to change gender normative structures, making possible yet other and freer gender performances.